A Review on Applications of Kenaf Fibre Reinforced Composites - Gnanasekaran, Sasikumar; Ayyappan, Sivasangari (Asian Journal of Engineering and Applied Technology, 2018)
Natural fibres namely sisal, jute, kenaf, hemp, abaca and banana are mainly used in industries for developing Natural fibres composites. They find many applications such as automobiles, furniture, packing and construction due to many merits such as their low cost, good mechanical properties, non-toxic, low weight, less damage to processing equipment, improved surface finish, abundant and renewable resources. The objective of this paper is to review the applications of various kenaf fibre reinforced polymer composites which will provide a base for further research in this area.